Hamlet - Olivier, Laurence; Herlie, Eileen; Sydney, Basil; Simmons, Jean; Aylmer, Felix; Carlton Video Ltd.; Two Cities Film Production (London : Carlton Video Ltd., 2001)
Seldom has tragic story of the Danish prince tortured by his dutty to his murdered father and by the guilt and fear he feels at the prospect of revenge, been so brilliantly portrayed. It is the tragedy of a man who thinks but fails to act.
DVD, Region 2 / UK, Dolby Digital mono, Aspect ratio 4:3.
English language soundtrack with optional subtitles in English.
Laurence Olivier, Eileen Herlie, Basil Sydney, Jean Simmons, Felix Aylmer.
Produced and directed by Laurence Olivier.
Videodisc release of the original 1948 feature film.
Special features: Interactive Menus, Scene Access.
Keywords: Hamlet (Legendary character) -- Drama; Feature films; Video recordings for the hearing impaired